Guillain-Barré syndrome in southern China: retrospective analysis of hospitalised patients from 14 provinces in the area south of the Huaihe River. Issue 6 (11th January 2018) - Liu, Shuping; Xiao, Zheman; Lou, Min; Ji, Fang; Shao, Bei; Dai, Hongyuan; Luo, Can; Hu, Bo; Zhou, Ruiling; Zou, Zhangyu; Li, Jing; Li, Xiaoyi; et al.
Abstract : Objectives: The clinical and epidemiological profiles of Guillain-Barré syndrome (GBS) in southern China have yet to be fully recognised. We aimed to investigate the subtypes of GBS in southern China, compare the clinical features of demyelinating form with that of axonal form and test whether preceding infections and age have influence on the clinical phenotype, disease course and severity of GBS. Methods: Medical records of patients with a diagnosis of GBS admitted to 31 tertiary hospitals, located in 14 provinces in southern China, from 1 January 2013 to 30 September 2016, were collected and retrospectively reviewed. Results: Finally. 1056 patients, including 887 classic GBS and 169 variants, were enrolled. The 661 classic patients with available electromyographic data were grouped as having acute inflammatory demyelinating polyneuropathy (AIDP, 49.0%), acute motor axonal neuropathy (AMAN, 18.8%), inexcitable (0.9%) and equivocal (31.3%). In contrast to AIDP, patients with AMAN were characterised by earlier nadir (P=0.000), higher Hughes score at nadir (P=0.003) and at discharge (P=0.000). Preceding upper respiratory infections were identified in 369 (34.9%) patients, who were more inclined to develop AIDP (P = 0.000) and Miller-Fisher syndrome (P = 0.027), whereas gastrointestinal infection were found in 89 (8.4%) patients, who were more prone to develop AMAN (P=0.000), with more severe illness (P=0.001) and longer hospital stay (P=0.009). Children (≤15 years) and the elderly (≥56 years) were more severe at nadir, the elderly had the longest hospital stay (P=0.023). Conclusion: AIDP is the predominant form in southern China, which is different from data of northern China. The different subtypes, preceding infection and age of onset can partially determine the disease progression, severity and short-term recovery speed of GBS. Clinical trial registration: ChiCTR-RRC-17014152.